1989
DOI: 10.1017/s0031182000061126
|View full text |Cite
|
Sign up to set email alerts
|

Theilerial parasites isolated from carrier cattle after immunization withTheileria parvaby the infection and treatment method

Abstract: Groups of cattle were immunized with 10(-2) dilutions of sporozoite stabilates of Theileria parva lawrencei derived from African buffaloes either alone or in combination with Theileria parva parva derived from cattle and concomitant treatment with either long or short-acting formulations of oxytetracyline. At 90 or 120 days after infection, uninfected Rhipicephalus appendiculatus nymphal ticks were applied to individual immunized cattle and the resultant adults ticks were applied to individual susceptible catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Currently immunization by the infection and treatment method using live vaccines based on infective sporozoite stages of the parasites is so far the most prominent method [7,8,28,45,58,[65][66][67][89][90][91]. In this regard, the Katete and Chitongo stocks have successfully been used in the Eastern and Southern Provinces of Zambia, respectively.…”
Section: Theileriosismentioning
confidence: 99%
See 1 more Smart Citation
“…Currently immunization by the infection and treatment method using live vaccines based on infective sporozoite stages of the parasites is so far the most prominent method [7,8,28,45,58,[65][66][67][89][90][91]. In this regard, the Katete and Chitongo stocks have successfully been used in the Eastern and Southern Provinces of Zambia, respectively.…”
Section: Theileriosismentioning
confidence: 99%
“…Studies have shown that immunized cattle are protected against challenge provided the appropriate parasite stocks are used [91,112]. It is also known that immunized cattle as well as those that recover naturally from ECF/ CD are carriers of the infection and therefore, can serve as a source of infection for others [22,23,39,45,112]. These vaccines are poorly adopted in the region, mainly because of problems associated with the use of live parasites.…”
Section: Theileriosismentioning
confidence: 99%
“…However, this vaccine needs a cold chain for transportation and storage which leads to a huge increase in its cost (approximately $8–12 per dose). Further, some vaccinated cattle, especially immunocompromised cattle, remain as a source of transmission of parasites to other cattle ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, most of what is known about the tick-borne acquisition and transmission of T. parva by R. appendiculatus has been gathered through laboratory studies of cattle undergoing the short-lived acute stage of infection [ 9 – 14 ]. Animals that recover from acute disease can remain persistently infected and serve as reservoirs for R. appendiculatus ticks [ 15 ]. In areas where natural transmission occurs, a phenomenon known as endemic stability has been described as “a climax relationship between host, agent, vector and environment in which all coexist with the virtual absence of clinical disease” [ 1 ].…”
Section: Introductionmentioning
confidence: 99%